Komunikasi Nonverbal Guru dalam Berinteraksi dengan Siswa di Sekolah Luar Biasa Negeri 1 Kota Binjai - Anwar, M. Fachri; Indra, Farhan (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2024)
This study aims to identify the forms of nonverbal communication used by teachers in interacting with students at Sekolah Dasar Luar Biasa Negeri 1 Kota Binjai, analyze the meaning and function of nonverbal communication, and describe students' responses to nonverbal communication used by teachers. The research method used is a qualitative research method with a descriptive approach. Data collection was done through observation, interviews and documentation. Data analysis used is in the form of data reduction, data presentation, and conclusion drawing. The results showed that teachers at Sekolah Luar Biasa Negeri 1 Kota Binjai used several forms of nonverbal communication in interacting with students, including eye contact, body language, touch and facial expressions. The nonverbal communication has meaning and function, such as giving attention, motivation, and building closeness with students. Students respond positively to the nonverbal communication used by teachers, showing enthusiasm and engagement in learning.